Beliefs of herbal therapies of the community of the Ilam city of Ilam province, Iran - Amir S. Mozaffari Nejad; Mahmoud Bahmani; Naseer A. Shah; Sayed A. Shah; Mahmoud Rafieian-Kopaei (GarVal Editorial Ltda., 2018)
Context: Documenting folk uses of wild medicinal plants provide an important baseline for the future novel drugs development and pharmacological evaluation. Aims: To document the traditional ethnomedicinal knowledge of Ilam city of Ilam Province, Iran. Methods: Semi-structured interviews were carried out in the study area from 190 informants to document the ethnomedicinal knowledge during 2008-2014. The collected data were assessed with quantitative tools viz. medicinal use value (MUV), family use value (FUV) and relative frequency of citation (RFC). Results: A total of 132 plant species distributed in 116 genera and 51 families were revealed to be used in herbal-based therapy. The highest medicinal plants diversity was shown by Compositae (19 species). A total of 13 types of plant parts were reported to be used in different recipes dominated by leaf (31%). Highest MUV were shown by Alhagi maurorum Medik. (0.87) and Cannabis sativa L. (0.85). In case of RFC, the highest RFC were expressed by Lycium depressum (0.95) followed by Pistacia khinjuk (0.94), Nasturtium officinale (0.93) and Portulaca oleracea (0.90). Highest FUV among small families was shown by Cannabaceae (0.85) and among the large families by Leguminosae (0.55). Conclusions: The study revealed a high medicinal plant diversity that is utilized for long time by the local communities of Ilam to resolve their health-based problems. The plants marked in the present paper could be brought under pharmacological evaluation to further exploit their efficacy. This paper could be an important document for the future generations of the Ilam province, Iran.